A Study in Conceptual Parallels: Graeco-Roman Binding Spells and Babylonian Incantation Bowls - Saʿar, Orṭal-Paz (Aramaic studies, 2015)
This article explores the similarities and differences between Babylonian incantation bowls and Graeco-Roman binding spells and ‘prayers for justice’. It does not intend to demonstrate a direct historical link between the two, but rather to examine the conceptual relations between magical texts and artefacts stemming from different cultures.